2005
DOI: 10.1002/jsfa.2304
|View full text |Cite
|
Sign up to set email alerts
|

The phenolic acid and polysaccharide composition of cell walls of bran layers of mature wheat (Triticum aestivum L. cv. Avalon) grains

Abstract: The purpose of this study was to examine the carbohydrate and phenolic-ester composition of cell walls in wheat bran layers. Four defined layers of wheat bran were separated manually from mature grains of wheat (Triticum aestivum L. cv. Avalon) to give samples of beeswing bran (outer pericarp), cross cells, testa + nucellar epidermis and aleurone cells. The cell-wall material from each layer, and from a sample of intact bran, was analysed for carbohydrates and wall-bound esterified phenolic acids. The cell-wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
109
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(120 citation statements)
references
References 33 publications
10
109
0
1
Order By: Relevance
“…In the porcino flour the situation is opposite and free phenolics were 28.3 times higher than bound phenolics. This indicates that the phenolics in the investigated wheat flour sample are mainly present in a bound form, as earlier investigation by Paker, et al [7] also showed, while in the porcino flour phenolics are mainly present in a free form. Comparing the contents of phenolics in wheat and porcino flours, the content of free phenolics and the content of total phenolics (obtained by content summation of free and bound phenolics), was higher in the porcino flour than in the wheat flour.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In the porcino flour the situation is opposite and free phenolics were 28.3 times higher than bound phenolics. This indicates that the phenolics in the investigated wheat flour sample are mainly present in a bound form, as earlier investigation by Paker, et al [7] also showed, while in the porcino flour phenolics are mainly present in a free form. Comparing the contents of phenolics in wheat and porcino flours, the content of free phenolics and the content of total phenolics (obtained by content summation of free and bound phenolics), was higher in the porcino flour than in the wheat flour.…”
Section: Resultssupporting
confidence: 80%
“…free [6]. Phenolic acids represent the most common compounds of phenolics in wheat and are present mainly in bound forms, linked through the ester bond to the cell wall structural components such as cellulose, lignin and proteins [7]. The bound phenolics are considered to have a greater antioxidant capacity because they escape from gastrointestinal digestion along with the cell wall materials and are absorbed into the blood plasma during digestion by intestinal micro flora [1].…”
Section: Introductionmentioning
confidence: 99%
“…The carbohydrate composition of wheat bran (Fig. 6) clearly indicates that the nucellar layer has a higher ratio of Xyl to Ara than all the other bran tissues (Parker et al, 2005), which means that this tissue is highly susceptible to xylanase degradation. Thus, the location of XIPs in these high-Xyl tissues highlights their importance in protecting the inner layer and endosperm from biotic attack.…”
Section: Discussionmentioning
confidence: 99%
“…There were large differences between the sorghum and maize phenolic acid contents despite the two cereal grains being similar in structure, chemical composition and basis for grain hardness 17 . The differences in the diferulic acids content and composition of sorghum and maize cultivars could be due to variations in their biosynthesis and cross-linking hence affecting the degree of alkaline hydrolysis and breakage of ether bonds 18 . The time for extraction could have been insufficient to break all the sorghum ether bonds and release the diferulic acids despite the likelihood that the temperature generated would enhance mass transfer by increasing solid solubility and diffusion of solubilised phenolic acids into the alkali and reduce extraction time 19 .…”
Section: Quantitation Of Microwave Extracted Bound Phenolic Acids Of mentioning
confidence: 99%